New varieties of arid fruits (Current Horticulture, 2024)
Bael Thar Bhavya: Its yield is 97.18 kg/plant in 10th year,each fruit weighing 0.65-0.78 kg,fruit size 11.15 cm × 10.24cm, fruit girth 37.43-39.25cm, shell thickness 0.16-0.18 cm, total number of seeds 56.25, fibre weight 38.00g, shell weight 97.17-105.00g, locules in cross section 14-16,pulp TSS 32.47-34.15°Brix, TSS mucilage 45.12-49.50°Brix, acidity 0.31-0.33% and vitamin C 19.24-21.63 mg/100g pulp. It is mid maturing variety (4th weekof April). Compact canopy, short in stature and semi-spreading growth habit, highly suitable for high density (5m × 5m) planting. The fruits have very good shelf life (10-15days) and suitable for sherbet and slice. It is highly suitable for nuclear family.
Keywords: Drumstick Thar Tejas; magnesium; Bael Thar Gauri